Pengembangan Sistem Aplikasi Manajemen Proyek menggunakan Kanban Framework - Nurul Faizah; Nurudin Santoso; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
A project is a temporary activity that has a limit of time, scope and cost. Projects have many types, one of which is software project. Software house work on various types of software project. Each type of a project has different stages to develop according to the provisions of the software house or a project manager. In the same time, software house usually works at least 1-3 projects divided into several team. Each project is led by different project manajer in which, a project manager on particural project can be a team member of another project. A project manager is confused to monitor the progress of the project he leads and work on other projects. The solution provided is to build a system that can manage a project using kanban for management that can help the project manager and team member. By using kanban, a project manager can visualize each stages to complete a project. In this research the system development using Rapid Application Development (RAD) method with Object-Oriented (OO) approach and build on website platform. Testing on this system has been successfully tested including unit testing and integretion testing using basis path in white-box testing and validation testing in black-box testing and compatibility testing run well in 6 different browsers.